Pengaruh senam jantung sehat terhadap tekanan darah pada lansia di Panti Sosial Tresna Werdha Sinta Rangkang - Widhiyanto, Hendrykus Theo Damar; Kahanjak, Donna Novina; Patricia, Tisha; Balyas, Abi Bakring; Komara, Nisa Kartika (Fakultas Kedokteran Universitas Palangka Raya, 2024)
In the elderly who have decreased organ function, uncontrolled high blood pressure can cause many health problems if not addressed immediately. Healthy heart exercise is recommended as one type of exercise that can be done because it has many benefits for heart health and is easy to do at an affordable cost. Knowing the effect of senam janrung sehat on blood pressure in the elderly at Sinta Rangkang Tresna Werdha Social Home. This research is a quasi-experimental study with a one group pre-test post-test design. Sampling was carried out using purposive sampling technique with a total of 23 respondents. Given a senam jantung sehat intervention for 2 weeks with a frequency of 2 times a week. Bivariate data analysis using paired t test. There was a decrease in mean systolic and diastolic blood pressure pretest (164.87/89.39 mmHg) and posttest (147.52/81.57 mmHg). The results of the paired t test at the level of significance α 0.05 obtained a P value of 0.000. There is an effect of healthy heart exercises on blood pressure in the elderly at the Tresna Werdha Sinta Rangkang Social Home.